The (Hidden) Cost of Employer Parking Policies - Jos van Ommeren; Derk Wentink (Tinbergen Institute, 2010)
It has been argued that urban planning policies, through minimum parking requirements, and income tax policies induce free employer parking. We show that tax policies induce welfare losses in the order of 12% of parking resource costs, implying an annual deadweight loss in the order of exteuro 5 billion for Europe. In the US, due to the presence of minimum parking requirements, the deadweight loss of policy is even higher and in the order of 30 billion.
Keywords: R41; 330; employer parking; tax distortion; urban planning policies; Ruhender Verkehr; Betriebliche Sozialleistungen; Einkommensteuer; Steuerinzidenz; Wohlfahrtsanalyse; Kommunalplanung; Niederlande; USA